EFEKTIVITAS QUANTUM TEACHING LEARNING PADA MATA PELAJARAN MATEMATIKA SISWA SEKOLAH DASAR - Sholihah, Octarina Hidayatus (Universitas Muhammadiyah Surakarta, 2017)
Â The purpose of this research is to examines the effectiveness of quantum teaching learning by comparing the final results between students who use quantum teaching learning and without use quantum teaching learning at elementary school level learning. This research use a quasi-experimental research with a quantitative approach. The research design was Posttest Only Control Group Design by using quantum teaching learning in the experimental group discussion and lecture method in the control group. The population was all students in six grade of SDN Pojoksari academic year 2015/2016. The sampling technique used was cluster random sampling. Data collection methods used in this research is documentation and testing. Analysis data techniques in this research using t-test significance level of 5%. The result of this research is quantum teaching learning effective applied to elementary school mathematics courses.